Designing an Integrated Healthy Food Business Strategy at Griya Sehat Annaba Makassar Using QSPM - Irvan Afiat; Fahrul Riza; Eric Harianto (Publikasi Indonesia, 2025)
The growing public awareness of healthy lifestyles presents a strategic opportunity for complementary therapy service providers to innovate through nutrition-based services. This study aims to identify customer perceptions and preferences regarding the integration of healthy food services into Griya Sehat Annaba Makassar, analyze its strengths and challenges, and formulate optimal implementation strategies. Employing a Quantitative methods approach, primary data were collected through questionnaires from 96 clients and Focus Group Discussion with five key participants, including the owner and therapists. Quantitative data were analyzed using descriptive statistics, validity and reliability testing, and strategic mapping through SWOT, TOWS, and QSPM approaches through Focus Group Discussion. The findings indicate that most clients have a favorable perception and high interest in the healthy food service, with trust in therapists and perceived health benefits serving as key determinants. The prioritized strategy emphasizes the development of personalized therapy-based services and collaboration with local partners. The study contributes theoretically to the development of nutrition-based alternative health service integration through a consumer behavior perspective. It offers a practical strategic model for community-based health service providers and entrepreneurs. It also recommends expanding digital-based services and strengthening human resource training as a means of enhancing the sustainability of the integration system.